Storytelling as increasing knowledge of dental health in kindergarten - Amelia Dwi Puteri; Emini Emini (Journal Center of Excellent : Health Assistive Technology, 2023)
Background: The results of the 2018 Basic Health Research stated that 93%. One of the factors that cause tooth decay in children is knowledge. Efforts that can be made to increase dental health knowledge in school children can be done by providing dental health education. One method of providing health information to school-age children is the storytelling method. Purpose: To analyze the effectiveness of storytelling as a method for dental health education on dental health knowledge in kindergarten children. Methods: The type of research used in this study was a quasy experiment with a pretest and posttest design with one group design. This research was conducted at the Putradarma Modern Islamic Kindergarten. The sampling technique used a total sampling of 33 students. Independent variable: storytelling method and dependent variable: dental health knowledge. Data analysis was tested using paired sample t test. Result: The results of this study indicate that the average value of dental health knowledge before being given education using the storytelling method is 7.52 and after being given education using the storytelling method is 8.97, with the results of paired sample t-test p <0.001 Conclusion: storytelling is effective as a method of dental health education in increasing dental health knowledge. Conclusion: Storytelling effective as a dental health education method in increasing dental health knowledge.